Optimization of Regional Original Revenue at the Regional Transportation Agency of North Sulawesi Province - Polii, Sendy Harland Pradhana; Bogar, Wilson; Bulo, Laurens (Technium Social Sciences Journal, 2025)
This study aimed to examines the efforts to optimize Regional Original Revenue (PAD) through port service levies at the North Sulawesi Provincial Transportation Agency. Given North Sulawesi’s strategic position as an archipelagic trade and logistics hub, port service levies represent a critical source of regional financing. Despite the potential, PAD from port levies has consistently underperformed relative to targets, reflecting structural, technical, and administrative constraints. Using a qualitative approach, data were collected through in-depth interviews, observation, and document analysis with key stakeholders, including agency officials, field officers, and port service users. The analysis focused on five indicators: levy collection effectiveness, administrative and operational efficiency, levy potential, constraints and challenges, and optimization strategies. Findings indicate that while administrative procedures are standardized and supported by digital applications, full digitalization has not been achieved, limiting operational efficiency. The potential for levy revenue remains underutilized due to incomplete data, weak inter-agency coordination, and regulatory gaps that restrict local authority. Structural issues such as overlapping authority, insufficient technical support, and limited human resource capacity further hinder optimization. Budget constraints emerged as the most critical determinant, restricting routine monitoring, data collection, and field supervision, particularly in remote and archipelagic areas. Strategies to enhance levy collection emphasize regulatory adaptation, managerial capacity building, and technological modernization through integrated digital systems. Strengthening inter-agency coordination, improving human resources, and implementing evidence-based governance are essential to closing the implementation gap. This study highlights that optimizing port service levies requires a multidimensional approach, integrating legal, fiscal, technological, institutional, and social factors to enhance regional fiscal autonomy and support sustainable development in North Sulawesi.